Analysis of Income Level of Cocoa Farmers in Supporting Regional Development in Iwoimendaa District, Kolaka Regency, Southeast Sulawesi Province - Marsuni, Nur Sandi; Ahmar, Ainun Asmawiyah (Jurnal Ekonomi Balance, 2018)
This study aims to determine the income of cocoa farmers from 2012 to 2016 and to find out how much cocoa farmers' income contributes to regional development in iwoimendaa sub-district. This type of research is quantitative and qualitative research, data collection using survey method with questionnaire distribution to 44 cocoa farmers who are taken randomly. The income analysis data is managed using the farm income formula and the contribution analysis data is managed using the formula of contributions proposed by J. Simanjuntak quoted by Moch. Nazir. Data processing shows the income of cocoa farmers experienced a decrease, a very drastic decline occurred in 2013 and 2014, which initially in 2012 amounted to Rp. 745,375,000 dropped to Rp. 402.025.000 in 2013 and decreased again to Rp. 74.250.000 in 2014, but in 2015 the farmer's income rose to Rp. 76.7 million, and in 2016 to Rp.79.150.000. and the contribution of cocoa farmers income to regional development is quite big in 2013 with contribution of 134.57%, and the smallest occurred in 2016 with a contribution of 7.89%.